2013
DOI: 10.3378/027.085.0308
|View full text |Cite
|
Sign up to set email alerts
|

Admixture Patterns and Genetic Differentiation in Negrito Groups from West Malaysia Estimated from Genome-wide SNP Data

Abstract: Southeast Asia houses various culturally and linguistically diverse ethnic groups. In Malaysia, where the Malay, Chinese, and Indian ethnic groups form the majority, there exist minority groups such as the "negritos" who are believed to be descendants of the earliest settlers of Southeast Asia. Here we report patterns of genetic substructure and admixture in two Malaysian negrito populations ( Jehai and Kensiu), using ~50,000 genomewide single-nucleotide polymorphism (SNP) data. We found traces of recent admix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…This suggests more recent gene flow between them and their neighboring populations, most likely Malays. A similar observation was reported in Jehai, a Negrito subgroup using a less SNP ( Jinam et al 2013 ).…”
Section: Discussionsupporting
confidence: 84%
“…This suggests more recent gene flow between them and their neighboring populations, most likely Malays. A similar observation was reported in Jehai, a Negrito subgroup using a less SNP ( Jinam et al 2013 ).…”
Section: Discussionsupporting
confidence: 84%
“…Subsequent studies reported various demographic and evolutionary factors that affected their genetic diversity. These included admixture ( Jinam et al 2013 ), long term isolation and bottlenecks ( Deng et al 2014 ; Aghakhanian et al 2015 ), and adaptation to malaria ( Liu et al 2015 ). However, compared with Malaysian Negritos, genome-wide studies involving the Philippine Negritos are relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…Among descendants of the migrants, Papuans, aboriginal Australians, and Philippine Negritos show a larger amount of introgression of genomic fragments with Denisovan ancestry than the other East Asians, including Andamanese (Onge) and Malaysian Negritos (Jehai). This suggests that archaic humans related to the Denisovan lived somewhere in (or nearby) Southeast Asia (Reich et al, 2011;Jinam et al, 2013Jinam et al, , 2017. When East Asian populations are clustered as a tree with no assumption of migration between populations, most East and Northeast Asian populations form a single cluster, with Papuans, Australians, and Onge people at root positions, suggesting that the Southern route predominantly shaped the genetic features of present-day East and Northeast Asian populations (HUGO Pan-Asian SNP Consortium, 2009;Mallick et al, 2016;Lipson and Reich, 2017;).…”
Section: Upper Paleolithic Southern Migration Routementioning
confidence: 99%